Across time and space: Effects of urbanization on corticosterone and body condition vary over multiple years in song sparrows (Melospiza melodia). Issue 2 (February 2015) - Foltz, Sarah L.; Davis, Jason E.; Battle, Kathryn E.; Greene, Virginia W.; Laing, Brenton T.; Rock, Ryan P.; Ross, Allen E.; Tallant, James A.; Vega, Rene C.; Moore, Ignacio T.
Abstract: Animals inhabiting urban areas must simultaneously cope with the unique challenges presented by this novel habitat type while exploiting the distinctive opportunities it offers. The costs and benefits of urban living are often assumed to be consistent across time, but may in fact vary depending on the habitat features influencing them. Here we examine the glucocorticoid levels and body condition of song sparrows ( Melospiza melodia) resident at urban and rural sites over four consecutive years to determine whether these traits, which may be linked to the relative costs and benefits of these respective habitats, are consistent over time. Glucocorticoid levels and body condition varied by year in both habitat types. While habitat alone did not influence glucocorticoid levels, there was a significant interaction between year and habitat, indicating that glucocorticoids differ between habitats in some years but not others. There was no discernable effect of habitat alone on body condition. Overall, these data suggest that the costs and benefits of inhabiting urban versus rural habitats differ substantially from year to year. J. Exp. Zool. 323A: 109–120, 2015 . © 2015 Wiley Periodicals, Inc.